Albumin as an Effective Auxiliary Agent for the Enriched Extraction of Anthraquinones and Curcumin from Plant Matrices - Chiara Collevecchio; Salvatore Genovese; Francesco Epifano; Lorenzo Marchetti; Serena Fiorito (Molecules)
Nowadays, several processes to enrich desired bioactive compounds in plant extracts have been developed. The objective of the present study was to assess the performance of bovine serum albumin in increasing the extractive yields of anthraquinones and diarylheptanoids from their respective raw plant powder extracts. Aloe emodin, rhein, emodin, and chrysophanol, from Polygonum cuspidatum, Senna alexandrina, Rhamnus frangula, and Rheum palmatum, and curcumin from Curcuma longa were analyzed in parent dry extracts, solubilized either with water, ethanol, or hydro-alcoholic mixtures, and in ones treated with aqueous solutions of bovine serum albumin by HPLC with UV/Vis detection. The different ratios between the volumes of solvents, powdered plant extracts, and bovine serum albumin were tested. The addition of albumin provided an increase in the yields of aloe emodin in the range 7.8–50.4-fold; of rhein in the range 6.1–14.1-fold; of emodin in the range 19.7–39.7-fold; of chrysophanol in the range 15.1–28.7-fold; and, finally, of curcumin of 32.1-fold. The addition of bovine serum albumin in the processing of plant extracts has been shown to be a novel and a valid alternative, comparing favourably to already reported methodologies. The easy-to-handle procedures, readily accessible facilities, and the employment of cheap substrates and reagents represent the most evident advantages of the methodology described herein.